Enhancing Elementary Students' Interest in Physical Geography: The Development of BENAPRO PBL-Based Interactive E-Module - Anggun Febriyanti; Arina Restian (FKIP Universitas Lampung, 2026)
The challenge in teaching Natural and Social Sciences (IPAS) in elementary schools often lies in the difficulty of visualizing abstract concepts, particularly regarding landscape diversity and its relationship to community professions. Preliminary observations at Dadaprejo 01 Public Elementary School revealed a critical issue: fourth-grade students exhibited low engagement, characterized by a lack of focus and visible boredom during conventional lessons that relied heavily on static worksheets. Consequently, this study aims to develop the